AN INTERIOR STUDY OF JOYOSURAN WARD OFFICE IN SURAKARTA- INDONESIA ON THE ASPECTS OF FUNCTIONS AND SPACE FORMING AND FILLING ELEMENTS - Oktavia Ayu Noor Hanifah; Agung Purnomo (Institut Seni Indonesia Surakarta, 2020)
Surakarta is a city that has 54 villages/wards spreading across five sub-districts, namely: Pasar Kliwon, Jebres, Banjarsari, Laweyan, and Serengan. The buildings of ward offices in Surakarta are fascinating because they are some of the works of human culture influenced by local culture. The Joyosuran Ward Office building is Joglo, a strong Javanese nuance intended as a sign of Solo city's distinctive identity. On average, pendapa at ward offices is glass-walled and appears open with two doors at the front and the back. The function of a ward pendapa is as a meeting space, village gatherings, and other meetings. The next building is the office. The style of the ward office building in Surakarta is colonial architecture, a term for buildings with a form (or outside impression) of Nusantara's (Indonesian) architecture and modern architecture adapted to the climate, building materials, and technology developed at the current time. This research aims to find out the functions, elements of the form, and space fillers of the Joyosuran Ward Office in Surakarta. The research method used in this research is an analysis method with an interior design approach conducted at Joyosuran Ward Office in Surakarta. Data collected from informants, literature, and objects/artifacts. The results show that the functions, elements of form, and space fillers of the Joyosuran Ward Office are a public service office under the lowest government level management. The buildings are a mixture of colonial and Javanese styles. The benefits of this research's results can be an essential source of information for the development of interior design studies and cultured public buildings